Проблемные аспекты защиты информационного суверенитета государства и перспективы его защиты в Украине - Задерейко, Олександр Владиславович; Задерейко, Александр Владиславович; Zadereyko, Olexandr V.; Троянский, Александр Вячеславович; Троянський, Олександр Вячеславович; Troyanskiy, Olexandr V.; Чечельницкий, Виктор Яковлевич; Чечельницький, Віктор Якович (My University, 2017)
В статье рассмотрены вопросы защиты информационного и цифрового суверенитетов государства как доминирующих составных частей традиционного суверенитета государства. Проанализированы существующие способы государственного контроля с целью сохранения информационного и цифрового суверенитетов государства. Даны рекомендации по защите информационного и цифрового суверенитета Украины.

У статті розглянуто питання захисту інформаційного та цифрового суверенітетів держави як домінуючих складових частин традиційного суверенітету держави. Проаналізовано існуючі способи державного контролю з метою збереження інформаційного та цифрового суверенітетів держави. Надано рекомендації щодо захисту інформаційного та цифрового суверенітету України.

Traditional conception of state sovereignty is the basis of ail modern system of international relations, in the last decades exposed to the systematic «attacks» from the side of row of the leading states. Thus, in modern realities, if the state does not have informative sovereignty and mechanism its defense, it can lose traditional sovereignty, that's why to leave off to be the independent state. Development of informatively-com- puter technologies comes forward to one of great number of factors of influence on sovereignty of the any state. That's why the protection of information and digital sovereignty of the state as the dominant constituent parts of the traditional sovereignty of the state. The classical attributes of any state it is been: territory, banking system, national money, army, power, police, borders, custom etc. The development of virtual of communication environment (kiberspace) new state attributes appeared - informative and digital sovereignties. Under informative sovereignty under- stands state possibility to manage information that comes to the population. Under digital sovereignty understands a right of the state to determine the informative politics independently, dispose of digital infrastructure and resources, to provide the state informative safety. The informative state sovereignty is guarantee to providing defense of its population from the massed informative treatment from the side of external opponent. Thus, if the state enters similar limitations for providing of the informative sovereignty, then it fully corresponds to the international legislation. Any state has existing methods of control on preservation of information and digital sovereignty of the state. An author gives recommendations for the protection of information and digital sovereignty of Ukraine.
Задерейко А. В. Проблемные аспекты защиты информационного суверенитета государства и перспективы его защиты в Украине / А. В. Задерейко, А. В. Троянский, В. Я. Чечельницкий // Юридичний науковий електронний журнал. - 2017. - № 2. - С. 10-13. - Режим доступу: http://lsej.org.ua/index.php/arkhiv-nomeriv
Keywords: информационный суверенитет; цифровой суверенитет; информационный щит; электронный щит; защита суверенитета государства; інформаційний суверенітет; цифровий суверенітет; інформаційний щит; електронний щит; захист суверенітету держави; information sovereignty; digital sovereignty; information board; electronic shield; protection of state sovereignty